It’s My (National) Stage Too: Sabina Berman and Jesusa Rodríguez as Public Intellectuals - Stuart A. Day (Studies in 20th & 21st Century Literature, 2008)
Based on interviews with Sabina Berman and Jesusa Rodríguez, this article offers a view of artists as public intellectuals in Mexico. These two prominent figures, in addition to staging biting commentaries on Mexican politics, have reached beyond the traditional theater to take on the role of public intellectuals (artists, activists, professors, performers, writers, among others, who speak truth to power) on the national stage, Berman through a book on the 2006 elections and her television program, Shalalá, and Rodríguez as the stage director for the massive public demonstrations of Andrés Manuel López Obrador. Both artists see the importance of reaching out to a wide audience; however, the 2006 elections and their wake have produced a rift in the political left, a rift that is exemplified by the public positions of Berman and Rodríguez. Their long-term, irreverent questioning of the status quo manifests itself in different forms: for Berman and other leftists López Obrador has come to represent the “statist, anti-sexual, anti-diversity, and pro-monopoly” left; whereas for Rodríguez vocal support of the politician represents a move from what she called the “map” (her cabaret space) to terra firma, the space of Mexicans in search of a better life.
Keywords: Sabina Berman; Jesusa Rodríguez; interview; public intellectuals; Mexico; Mexican politics; activists; tierra firma